A non-aqueous all-copper redox flow battery with highly soluble active species. (10th May 2017) - Li, Yun; Sniekers, Jeroen; Malaquias, João; Li, Xianfeng; Schaltin, Stijn; Stappers, Linda; Binnemans, Koen; Fransaer, Jan; Vankelecom, Ivo F.J.
Abstract: A metal-based redox pair with acetonitrile as ligand [Cu(MeCN)4 ][Tf2 N] is described for use in non-aqueous redox flow battery (RFB). The electrode kinetics of the anode and cathode are studied using cyclic voltammetry. The Cu 2+ /Cu + and Cu + /Cu couples in this system yield a cell potential of 1.24 V. The diffusion coefficient for [Cu(MeCN)4 ][Tf2 N] in acetonitrile is estimated to be 6.8 × 10 −6  cm 2  s −1 at room temperature. The copper-acetonitrile complex has a very high solubility of 1.68 M in acetonitrile, the most widely used organic solvent for non-aqueous electrochemical applications. Hence, a maximum theoretical energy density around 28 Wh L −1 can be reached with the reported system. The RFB with this electrolyte shows a promising performance, with coulombic efficiencies of 87% and energy efficiencies of 44% (5 mA cm −2 ).